Women's Participation in Sustainable Development in Teluk Sulaiman Village: an Ecofeminism Analysis - Bintang Daniswara Susanto; Khoirul Amin; Mohamad Dziqie Aulia Al Farauqi (Riviera Publishing, 2026)
Ecofeminism is a movement that considers gender equality and environmental sustainability as two important agendas in sustainable development. This research aims to analyse women's participation in achieving sustainable development goals (SDGs) 5 and 12 through an ecofeminism analysis in Kampung Teluk Sulaiman, Biduk-Biduk District, Berau Regency, East Kalimantan. This research uses a descriptive qualitative approach with data collection techniques including in-depth interviews, web articles about rural women, and literature reviews. The research findings indicate that women play a significant role in promoting social and ecological awareness within communities. Women directly participate in environmental behaviour change and improving the quality of life for communities. An analysis of ecofeminism reveals that values of care, empathy, and social responsibility form the basis of women's contributions to maintaining a balance between social and ecological life. Active participation by women reflects local success in strengthening gender equality while also promoting sustainable practices. Thus, empowering women at the community level has the potential to be an effective strategy for achieving ecological and social justice in line with the principles of sustainable development.